Monitoring cultural heritage sites affected by geohazards - Themistocleous, Kyriacos; Danezis, Chris (My University, 2018)
Currently, assessing geo-hazards in cultural heritage sites takes place after the geo-hazard has occurred. The long-term vulnerability of cultural heritage is commonly focused on the site itself, in response to environmental risks, without fully considering or understanding the entire geological and geotechnical context. However, the high costs of maintenance of cultural heritage sites directly enforce the prioritisation of the monitoring and conservation policies to ensure sustainable conservation. Monitoring the deformation of structures as well as their surroundings facilitates the early recognition of potential risks and enables effective conservation planning. This paper will present the results of the case study of the UNESCO World Heritage Site of Choirokoitia, Cyprus, where long-term low-impact monitoring systems such as UAVs and geodetic techniques were used to monitor and assess the risk from natural hazards on the archaeological site to evaluate potential geo-hazards.
Keywords: Cultural heritage; Geodetic techniques; Natural hazards; Remote sensing; UAV